2017
DOI: 10.3906/sag-1601-185
|View full text |Cite
|
Sign up to set email alerts
|

Relation between foot pain and plantar pressure in pregnancy

Abstract: Background/aim: Hormonal and structural changes that occur during pregnancy cause alterations in body biomechanics. These alterations reach their peak in the last trimester. Adaptive changes that appear in the foot result in pain in the foot and ankle. Pedobarography is a noninvasive measurement method that can be used to understand the origin of such pain. Materials and methods:One hundred and thirty-one pregnant women who did not have a foot or ankle problem prior to pregnancy volunteered to take part in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Therefore, the size of the force impulse is probably formed more by force than by time during the gait. Varol et al (2017) observed a general increase of FTI values during a pregnancy, especially in the midfoot area and this change could be related to increased foot pain.…”
Section: Tabmentioning
confidence: 82%
“…Therefore, the size of the force impulse is probably formed more by force than by time during the gait. Varol et al (2017) observed a general increase of FTI values during a pregnancy, especially in the midfoot area and this change could be related to increased foot pain.…”
Section: Tabmentioning
confidence: 82%
“…Physical and mechanical changes associated with pregnancy also are associated significantly with pain, for example, carrying the excess weight of pregnancy is associated with lower back pain or pelvic girdle pain 31,32 and with increased knee and foot pain. 33,34 Many disease states associated with maternal morbidity and mortality are painful or have the potential to exasperate existing pain states. Hemorrhage, cardiovascular and coronary conditions, infection, cardiomyopathy, embolism, preeclampsia and eclampsia, and mental health conditions are the leading causes of death associated with pregnancy in the United States.…”
Section: Pain and Pregnancymentioning
confidence: 99%
“…Previous research into the gait biomechanics of pregnant women referred to kinetic variables, such as ground reaction forces [2,9], kinematics [2,[10][11][12][13], spatiotemporal parameters [9,[14][15][16][17][18][19], and plantar pressure distribution [13,17,[19][20][21][22][23][24][25]. More literature about LBP, posture, and gait changes during pregnancy has been assessed in some interesting reviews [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…No significant correlation was observed between LBP and lumbar lordosis [1,29] or lower limb pain and pronated foot posture [30]. A weak correlation was also found between foot pain and forefoot contact time but no correlation with plantar pressure [14], whereas higher forces in the midfoot and a broader contact area were correlated to the presence and severity of foot pain [25]. Reported results can be used to understand the musculoskeletal dysfunctions of pregnant women to design exercises for the preventive and rehabilitative treatment of pain [31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation